2021
DOI: 10.3390/nu13051666
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of a High Fat Diet on Bone in Skeletally Mature and Developing Male C57BL/6J Mice

Abstract: Increased risks of skeletal fractures are common in patients with impaired glucose handling and type 2 diabetes mellitus (T2DM). The pathogenesis of skeletal fragility in these patients remains ill-defined as patients present with normal to high bone mineral density. With increasing cases of glucose intolerance and T2DM it is imperative that we develop an accurate rodent model for further investigation. We hypothesized that a high fat diet (60%) administered to developing male C57BL/6J mice that had not reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…( 55 , 56 , 57 ) In addition, hyperglycemia mice induced by high‐fat diet showed reduced biomechanical strength of trabecular and cortical bone with reduced expression of osteocalcin, as which the finding supported bone loss in hyperglycemia mice due to decreased bone formation (osteoblast function). ( 58 ) Therefore, decreased bone metabolism is probably the underlying mechanism driving the reduction of BMD in our OVX rats. This finding reveals the fact that there may be different subtypes of osteoporosis in postmenopausal women based on the severity of metabolic conditions and, therefore, the specific therapeutic approach should be considered for those subtypes.…”
Section: Discussionmentioning
confidence: 84%
“…( 55 , 56 , 57 ) In addition, hyperglycemia mice induced by high‐fat diet showed reduced biomechanical strength of trabecular and cortical bone with reduced expression of osteocalcin, as which the finding supported bone loss in hyperglycemia mice due to decreased bone formation (osteoblast function). ( 58 ) Therefore, decreased bone metabolism is probably the underlying mechanism driving the reduction of BMD in our OVX rats. This finding reveals the fact that there may be different subtypes of osteoporosis in postmenopausal women based on the severity of metabolic conditions and, therefore, the specific therapeutic approach should be considered for those subtypes.…”
Section: Discussionmentioning
confidence: 84%
“…Accordingly, either SOST -knockout mice or sclerostin-neutralizing antibody-treated mice exhibit a phenotype characterized by increased bone mass and reduced white adipose tissue [ 19 ]. Ross et al reported decreased bone formation, decreased osteocalcin expression and increased sclerostin RNA expression in young and old HFD-fed mice compared to standard chow-fed mice, confirming the negative effect exerted by metabolic diseases on bone, including through the activation of sclerostin [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In animals, catch-up growth was demonstrated to promote insulin resistance through dysfunction of the adipose tissue [ 41 ]. In addition, it has also been shown that hyperinsulinemia, together with an impaired control of the blood glucose levels, is associated with decreased bone mass and defective bone microarchitecture [ 14 , 42 ]. In this sense, studies conducted in streptozotocin-induced diabetic adult rats, which are characterized by induced hyperglycemia, have observed that diabetic animals display lower BMD and connection density along with compromised bone microstructure compared to control healthy rats [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously commented, unhealthy catch-up growth correlates to higher risk of metabolic diseases, such as diabetes and obesity, later in life [ 7 ]. Moreover, diabetic, and obese adult patients are at higher risk of bone fractures due to impaired bone microstructure [ 42 , 46 ]. Overall, preventing the development of a thrifty phenotype characterized by impaired insulin sensitivity might exert short- and long-term beneficial effects on bone health parameters (i.e., BMD and bone trabecular and cortical microstructure) of children undergoing catch-up growth, leading to a higher peak bone mass at the end of their adolescence.…”
Section: Discussionmentioning
confidence: 99%